The Influence of Self Management Education through Booklet Media on the Self-Care Commitment of Type II Diabetes Mellitus Patients - Simangunsong, Berman Ridwan; Antoro, Budi; Putri, Dian Utama Pratiwi (Global Health Science Group, 2024)
Diabetes mellitus is the inability of the pancreas to produce enough insulin. The prevalence of DM in Lampung Province is 1.63 per 100,000 population with the highest incidence of diabetes mellitus, Mesuji Regency with a prevalence of 0.96 per 100,000 population. Proper self- management of diabetes mellitus can alleviate some of the physical and mental consequences of this disease. The purpose of this study was to determine the effect of self-management education through booklet media on the commitment to self-care of type II diabetes mellitus sufferers. Quantitative research type, pre-experimental design, one-group pretest-posttest approach. The population of patients suffering from type II diabetes mellitus was 134 patients, with a sample of 57 respondents using the purposive sampling technique. The study was conducted at the Outpatient Clinic of the Mesuji Regional General Hospital, Mesuji Regency in May-August. Univariate and bivariate data analysis (paired sample t-test).The results showed that the average self-care commitment of patients with type II diabetes mellitus before self management education through booklet media was 61.5 and after self management education through booklet media was 81.9. The results of the analysis test using paired sample t-test with a significance level of α = 0.05, found that the p-value = 0.000. Conclusion: There is an effect of self management education through booklet media on self- care commitment of patients with type II diabetes mellitus. Suggestions for health workers to be able to provide counseling activities for patients with diabetes mellitus using booklets which are one of the models in the standard of providing education.